Facebook addiction and sleep problems in peruvian university students after the COVID-19 pandemic - Joel Figueroa-Quiñones; Willy Valle-Salvatierra; Condor Heredia Nelly Teresa (Heliyon, 2024)
Background: During the COVID-19 pandemic, studies have reported an increase in sleep problems and problematic use of social media platforms such as Facebook among university students. This study assessed Facebook addiction and sleep problems among Peruvian university students following the COVID-19 pandemic, as well as the factors associated with these issues. Methods: A cross-sectional study was conducted with a sample of 352 participants from different regions of Peru. The Jenkins Sleep Scale (JSS-4) and the Bergen Facebook Addiction Scale (BFAS) were used to assess sleep problems and Facebook addiction, respectively. Prevalence ratios (PR) were calculated using a simple Poisson regression with robust variance. Results: The study found that 16.2 % of the participants were addicted to Facebook and 12.5 % reported sleep problems. The results also showed that older age (PR: 0.99; 95 % CI: 0.98–0.99) and physical activity (PR: 0.81; 95 % CI: 0.70–0.94) were associated with a lower likelihood of having sleep problems, while being physically active (PR: 0.55; 95 % CI: 0.33 to 0.90) was associated with a lower probability of having Facebook addiction problems. Conclusions: The Peruvian university students who participated in this study reported sleep problems in one-eighth of the sample, and one in six university students reported Facebook addiction problems. The frequency of presenting Facebook addiction and sleep problems was lower in those with older age and engaging in physical activity.